Scanning tunneling microscopy of electrochemically activated platinum surfaces : A direct ex-situ determination of the electrode nanotopography - Vázquez, L. (1987)
A direct scanning tunneling microscopy ex-situ determination on the nanometer scale of the topography of electrochemically highly activated platinum electrodes is presented. A correlation between catalytic activity and surface microtopography becomes evident. This result gives support to a structural model for the activated electrode surface. In the model, a volume with a pebble-like structure allows electrocatalytic processes to occur practically free of diffusion relaxation contributions under usual voltammetric conditions.